The Utilization of Digital Promotion as an Effort to Improve the Quality of Services and Training at the Center for Vocational and Productivity Training-Bandung - Martinicha Pareda Tondonaung; Prihartono Aksan Halim (Greenation International Journal of Economics and Accounting, 2025)
This study aims to analyze the utilization of digital promotion as a strategic effort to improve service quality and training quality at the Vocational and Productivity Training Center (BBPVP) Bandung. This research employed a quantitative descriptive analytical approach involving 28 respondents, consisting of prospective trainees, active participants, and alumni. Data were collected through observation and a Likert-scale questionnaire, and analyzed using validity and reliability testing, Spearman correlation, and multiple linear regression analysis. The results indicate that digital promotion is categorized as highly effective (mean = 4.50), as well as service quality (mean = 4.36) and training quality (mean = 4.46). The correlation analysis revealed a very strong and significant relationship between digital promotion and service quality (r = 0.987), and training quality (r = 0.897). The multiple linear regression model shows that service quality and training quality significantly influence digital promotion, with a contribution value of R² = 0.986, where service quality is the most dominant variable. These findings confirm that digital promotion not only functions as a medium for information dissemination, but also represents service excellence and training value, thereby playing an essential role in strengthening positive perceptions and enhancing institutional competitiveness.